Evaluation of Tonsillotomy Effects on Pharyngeal Volume and Compliance in Children. (February 2020) - Al Ali, Abeer; Bois, Emilie; Boujemla, Imene; Teissier, Natacha; Van den Abbeele, Thierry; Delclaux, Christophe; Bokov, Plamen
Our objective was to assess whether adenotonsillotomy improved pharyngeal compliance, which is a risk factor for sleep-disordered breathing. Otherwise healthy children underwent Obstructive Sleep Apnea (OSA)-18 questionnaire and a pre- and postoperative acoustic pharyngometry in both sitting and supine positions, allowing the measurement of the volume of the palatine tonsil region and pharyngeal compliance. Thirty-five children (median age 5.3 years) were enrolled; they were reevaluated at a median of 18 days (25th-75th percentiles, 15-25) after surgery. Participants were compared according to a normal (n = 18) or an increased (n = 17) preoperative pharyngeal compliance. Surgery was associated with a significant decrease in OSA-18 and Brodsky scores, with a median increase in palatine volume of 0.13 cm 3 (25th-75th percentiles, 0.00-0.73). A decrease in pharyngeal compliance was observed in children with increased preoperative compliance. The variation of palatine volume after surgery was positively related to the variation of pharyngeal compliance, suggesting that obstruction relief was associated with muscle relaxation in children with normal preoperative compliance.